2016
DOI: 10.1038/nature20791
|View full text |Cite
|
Sign up to set email alerts
|

Targeting metastasis-initiating cells through the fatty acid receptor CD36

Abstract: The fact that the identity of the cells that initiate metastasis in most human cancers is unknown hampers the development of antimetastatic therapies. Here we describe a subpopulation of CD44 cells in human oral carcinomas that do not overexpress mesenchymal genes, are slow-cycling, express high levels of the fatty acid receptor CD36 and lipid metabolism genes, and are unique in their ability to initiate metastasis. Palmitic acid or a high-fat diet specifically boosts the metastatic potential of CD36 metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
1,026
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,105 publications
(1,116 citation statements)
references
References 67 publications
38
1,026
1
3
Order By: Relevance
“…A subpopulation of cancer cells with high CD36 expression has unique metastasis-initiating potential, highlighting a key role of CD36-regulated lipid metabolism and signaling in metastatic colonization (45). Lysophosphatidic acid/protein kinase D1/CD36 signaling is a bona fide breast cancer promoter via stimulating microvascular remodeling in chronic diet-induced obesity (46).…”
Section: Discussionmentioning
confidence: 99%
“…A subpopulation of cancer cells with high CD36 expression has unique metastasis-initiating potential, highlighting a key role of CD36-regulated lipid metabolism and signaling in metastatic colonization (45). Lysophosphatidic acid/protein kinase D1/CD36 signaling is a bona fide breast cancer promoter via stimulating microvascular remodeling in chronic diet-induced obesity (46).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that the Warburg effect may contribute to the early stages of cancer progression. Instead, the reprogramming of fatty acid (FA) metabolism in cancer cells may provide a selective advantage toward the metastatic process [8,9]. FAs are the major building blocks for energy metabolism and represent the essential components of the signal transduction network of biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have studied the eff ect of titanium nitride and chromium disilicide nanoparticles on the expression of a subset of genes encoding different regulatory factors (IGFBP1, IGFBP2, IGFBP3, IGFBP4, IGFBP5, CD36, and PECAM1) and enzyme SNARK/NUAK2, which play an important role in various metabolic pathways and thus control the cell proliferation and apoptosis as well as angiogenesis and metastasis (Praveen Kumar et al 2014;Baxter 2015;Kim and Lee 2015;Musumeci et al 2015;Ding et al 2016;Kim et al 2016;Miller et al 2016;Phillips et al 2016;Guaita-Esteruelas et al 2017;Pascual et al 2017). For titanium dioxide nanoparticles, which are widely used in the number of applications, including cosmetic creams, toothpastes, and component of surgical implants, it has been shown that long-term exposure to these nanoparticles led to accumulation of these nanoparticles in brain, over-proliferation of glial cells and signifi cant changes in brain gene expressions as well as to neurogenic disease states in mice (Ze et al 2014;Rollerova et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that proteins encoded by all these genes play an important role in controlling of cell proliferation, apoptosis, cancer growth, and angiogenesis (Praveen Kumar et al 2014;Bach 2015;Baxter 2015;GuaitaEsteruelas et al 2017;Pascual et al 2017). Moreover, CD36 antigen may also play a role in the pathogenesis of impaired fasting glucose/impaired glucose tolerance and type 2 diabetes (Wang et al 2012).…”
Section: Igfbp3 Igfbp4mentioning
confidence: 99%
See 1 more Smart Citation